THE ROLE OF BANKING INNOVATION IN THE FINANCIAL MARKET IN THE CONDITIONS OF THE GLOBAL FINANCIAL SPACE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article identifies the concepts and types of banking innovations, establishes the main properties and characteristics that banking innovations must meet, identifies the benefits of their use for both banking institutions and consumers. The purpose of the article is to identify the concept of banking innovations, their types in banking, as well as the features of the application of innovative products in the practice of domestic and foreign banking institutions. It is established that the main modern banking innovations that operate in the financial market of Ukraine are technologies such as clouds, artificial intelligence, blockchain, Big Data. The paper also shows the impact of innovation on the banking sector of the financial system, as well as identifies the main benefits of the use of innovation by banking institutions: reducing the cost of periodic tasks; differentiation of banking products and services; obtaining additional revenue due to the introduction of innovative products; improvement of already existing banking products and services. Thus, among the main trends in banking innovation should be noted the shift of emphasis from price and quantity characteristics of financial products to service and quality characteristics, such as individual approach to the client, speed and quality of service. The bulk of customer inquiries focus on the extraterritoriality and continuity of systems, forcing banks to focus on management tools regardless of location and time of day, public access, multiple access channels and interactivity of service, real-time operations and minimization of manual processing. Innovations in these areas are due to both changing customer demand and the widespread development of information technology. Currently, the financial market and the market of P1-technologies are closely intertwined, and this interaction is bilateral. On the one hand, the development of new information technologies offers innovative solutions for the banking business, which can significantly increase the efficiency of the financial institution and improve the quality of services provided to customers and stimulates the emergence of certain innovations in the range of banking products and services.
Keywords: banking innovations, banking institutions, cloud technologies, artificial intelligence, blockchain, internet banking, cryptocurrency